2007
DOI: 10.1103/physrevd.75.054030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of new neutrino deep inelastic scattering and Drell-Yan data on large-xparton distributions

Abstract: New data sets have recently become available for neutrino and antineutrino deep inelastic scattering on nuclear targets and for inclusive dimuon production in pp and pd interactions. These data sets are sensitive to different combinations of parton distribution functions in the large-x region and, therefore, provide different constraints when incorporated into global parton distribution function fits. We compare and contrast the effects of these new data on parton distribution fits, with special emphasis on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 26 publications
1
46
0
Order By: Relevance
“…The parameterization of the presented nCTEQ nuclear PDFs is the same as in our previous analyses [13,21,33]. It mimics the parameterization used in the free proton CTEQ fits [34][35][36], and takes the following form:…”
Section: A Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameterization of the presented nCTEQ nuclear PDFs is the same as in our previous analyses [13,21,33]. It mimics the parameterization used in the free proton CTEQ fits [34][35][36], and takes the following form:…”
Section: A Parameterizationmentioning
confidence: 99%
“…The free proton PDFs are described by the coefficients c k,0 which in our analysis are fixed to values of the fit of Ref. [34] which is close to CTEQ6.1 [36] but has the advantage of having minimal influence from nuclear data. Although in principle this framework can be used to determine the strange quark content of the bound nucleon, there is not sufficient data available to reliably do that.…”
Section: A Parameterizationmentioning
confidence: 99%
“…A detailed study of these problems in the global analysis context, including effects of nuclear target corrections, has recently been performed in [25]. This open issue does not affect our study of the strange sector, since the strange distributions are insensitive to total inclusive cross sections, as demonstrated in sections 3 and 4.…”
Section: A Fixed Target Charged Current Dis Datamentioning
confidence: 99%
“…In regard to NuTeV data, an early study in Ref. [105] found that these data could be accommodated together with the CHORUS neutrino DIS data when constraining d/u ratio but with the applied nuclear corrections some pull against other DIS and DY data were observed. Later on, the analyses in Refs.…”
Section: Neutrino Dis Datamentioning
confidence: 99%